Transformasi Madrasah di Indonesia: Analisis Kurikulum, Kelembagaan, dan Tantangan Era Modern - Juliana Ezzy Hervaldi; Yowanda Naura Basitka; Safrina Amalia Putri; Sutrimo Purnomo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study discusses the dynamics of curriculum development, institutional growth, and the challenges faced by madrasahs within the Islamic education system in Indonesia. The objective of this study is to analyze the development of the madrasah curriculum over time, examine the institutional development of public and private madrasahs, and identify various internal and external challenges affecting the quality of madrasah education. The research method employed in this study is a qualitative method using a library research approach. The data were collected through the analysis of various academic sources, including books, journals, scholarly articles, government regulations, and educational policy documents relevant to the development of madrasahs in Indonesia. The data were analyzed using descriptive qualitative analysis by reviewing, classifying, comparing, and interpreting the findings based on historical, institutional, and educational policy perspectives. The results of the study indicate that the madrasah curriculum has undergone dynamic development in line with changes in national education policies, starting from traditional educational models to the implementation of the Independent Curriculum (Merdeka Curriculum), which emphasizes competencies, character building, literacy, and 21st-century skills. From an institutional perspective, public madrasahs have developed through state institutionalization policies and government support, while private madrasahs have grown through community initiatives with diverse institutional characteristics. This study also finds that madrasahs continue to face several challenges, including limitations in human resources, weak institutional governance, unequal educational facilities and infrastructure, and the demands of digital transformation. Nevertheless, madrasahs demonstrate adaptive capacity in maintaining their Islamic identity while adjusting to contemporary developments.